Reformulation of Islamic fiqh, Islamic state and Islamic revivalism: views of Hassan Alturabi - Eissa, Garoot Suleiman (IIUM Press, 2005)

(untitled)
Reviews ideas of Hassan Al-Turabi as a leading contemporary Isalamic intellectual who has some useful views on Islamic Political Issues and Islamic State.